Health-Related Quality of Life and 6 Min Walk Distance in Patients with Idiopathic Pulmonary Fibrosis - Geetika Verma; Theodore Marras; Noori Chowdhury; Lianne Singer (Canadian Respiratory Journal)
BACKGROUND: Few studies have investigated the relationship between physiological outcomes and quality of life in patients with idiopathic pulmonary fibrosis (IPF). Health-related quality of life (HRQL) data may provide a valuable patient-centred outcome for the evaluation of interventions. Determination of which physiological and functional variables are associated with HRQL may facilitate interpretation of disease progression and impacts of therapy.